Regulatory Indicators for Sustainable Energy 2020 : Sustaining the Momentum - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2020)
Regulatory Indicators for Sustainable Energy (RISE) 2020 monitors and assesses policy and regulatory support for sustainable energy to promote energy efficiency and the use of renewable energy while expanding access to electricity and clean cooking fuels. Marshalling policy data from well before the onset of the Coronavirus (COVID-19) pandemic through December 2019, RISE 2020 reviews what governments have done to create an enabling environment for sustainable energy.